The Islamic Perspective on Criminalization of Forced Marriage In Indonesia - AGUSTIAWAN, M. HENDRI; Muhammad Abdulloh Rohmad Aziz (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2023)
Forced marriage is a human rights violation that is widely practiced in various parts of the world, including Indonesia. This article aims to examine the Islamic perspective on the crime of forced marriage as regulated in Law Number 12 of 2022 concerning the Criminal Offense of Sexual Violence. This research is qualitative normative legal research analyzing laws and regulations in Indonesia and Islamic legal sources. The result of the study shows that Islam prohibits any form of forced marriage. Marriage must be based on the willingness and agreement of both parties. Perpetrators of forced marriage could be criminalized or sentenced to criminal sanction (takzir). Thus, Islam affirms the regulation of the criminal act of forced marriage as stated in Article Article 4 Paragraph (1) Letter e and Article 10 of Law of the Republic of Indonesia Number 12 of 2022 concerning Criminal Acts of Sexual Violence. By criminalizing forced marriages, Islamic principles reject all forms of destruction and defend the values of justice, equality, and beneficialness.